Exploration of New Double Peroviskites Cs2YInX6 (X = Cl, Br, I) for Opto-Electronic and Sustainable Energy Applications. (27th August 2021) - Mahmood, Asif; Noor, N. A.; Iqbal, M. Waqas; Al-Zahrani, Ateyah A.; Shin, Young-Han; Zahid, Tausif
Abstract : We used theoretical and computational methods to explore the double perovskites Cs2 YInX6 (X = Cl, Br, I) by having the scope and goal of finding their physical aspects and characteristic. To properly explain different phenomenological features of density functional theory (DFT), the ab-initio computational model based on the approximation of full-potential augmented plane wave plus local orbitals (FP-LAPW + lo) technique was implemented. The calculated ground state properties with GGA-PBEsol agree well with the available other theoretical data. Mechanical properties, another very important aspect of these double perovskites, are found by using shear modulus, Young's modulus, and Poisson's ratio. Further, we obtained bandgaps by investigating electronic properties with and without spin–orbit coupling (SOC). In order to calculate and compare the bandgaps with experimental results, we used SOC in connection with mBJ potential to investigate the direct bandgaps of Cs2 YInCl6 (Eg = 0.45 eV), Cs2 YInBr6 (Eg = 0.65 eV) and Cs2 YInI6 (Eg = 0.82 eV) respectively. Furthermore, optical properties are investigated in terms of calculations like complex dielectric constants ( ε ( ω )), refractive index (n( ω )), reflectivity (R( ω )) and absorption co-efficient ( α ( ω )) to find their possible applications in optoelectronic devices. In view of this background, BoltzTraP code will also be used to explore these double perovskites in respect of their thermoelectric applications.